2019
DOI: 10.1002/ece3.5534
|View full text |Cite
|
Sign up to set email alerts
|

Diel patterning in the bacterial community associated with the sea anemone Nematostella vectensis

Abstract: Microbes can play an important role in the physiology of animals by providing essential nutrients, inducing immune pathways, and influencing the specific species that compose the microbiome through competitive or facilitatory interactions. The community of microbes associated with animals can be dynamic depending on the local environment, and factors that influence the composition of the microbiome are essential to our understanding of how microbes may influence the biology of their animal hosts. Regularly rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…In addition, sampling of different body regions (physa, mesenteries and capitulum) of the adult revealed a specific microbiota for each region, with specific dominance of spirochaetes bacteria within the capitulum ( Bonacolta et al, 2021 ). Also changes in the diet lighting cycle induced differences in composition and relative abundance in N. vectensis microbiome ( Leach et al, 2019 ). It has also been observed that different life stages (larva, juvenile, and adult) host specific microbiota ( Mortzfeld et al, 2016 ; Domin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sampling of different body regions (physa, mesenteries and capitulum) of the adult revealed a specific microbiota for each region, with specific dominance of spirochaetes bacteria within the capitulum ( Bonacolta et al, 2021 ). Also changes in the diet lighting cycle induced differences in composition and relative abundance in N. vectensis microbiome ( Leach et al, 2019 ). It has also been observed that different life stages (larva, juvenile, and adult) host specific microbiota ( Mortzfeld et al, 2016 ; Domin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mice and human hosts rely on the daily relative abundance fluctuations of around 20% of their total microbiome species (Thaiss et al, 2014). However, under circadian disruption, these delicate gut microbial community compositions are significantly altered, leading to weakened immune defenses and holobiont health decline (Voigt et al, 2016;Deaver et al, 2018;Leach et al, 2019). Specifically, in the absence of rhythmic bacterial abundance fluctuations, hosts exhibit increased susceptibility to disease and decreased metabolomic output (Leone et al, 2015;Montagner et al, 2016;Thaiss et al, 2016).…”
Section: The Significance Of Mammalian Holobiont Rhythms For Innate Immune Response and Metabolic Activitymentioning
confidence: 99%
“…Alphaproteobacteria and Gammaproteobacteria constitute main microbial colonizers of corals 57,65 and of N. vectensis 18,66 . The increased thermal tolerance of animals acclimated at high temperatures is often associated with an increase in abundance of these bacterial classes in the associated microbiota 67,68 .…”
Section: Microbiota Plasticity Promotes Metaorganism Acclimationmentioning
confidence: 99%